Spain and Russia: Uncertain Factors in Doing Business - Sánchez-Torné, Isadora (2019)
The creation of companies has acquired great notoriety in the last ten years as a territorial instrument to counteract the dominant unemployment rates. Hence, this is one of the most decisive interventions between 1998-2018 by governments, which direct important efforts to promote and direct entrepreneurship. Business activity has a direct impact on a country’s economic growth, so it requires intervention on uncertain factors to start a business that represent limits to productivity and business competitiveness. Consequently, the objective of this investigation was to determine the most problematic factors detected by the managers of the relevant companies in the Russian (centralized) and Spanish (decentralized) economies. To this end, a descriptive and comparative statistical analysis was carried out based on the annual survey of the Wold Economic Forum during the period 2011-2016. The main findings indicated that the most problematic factors for Spain in relation to Russia were five, among which the Inefficient Government Bureaucracy and the Tax Rates stand out. In contrast, the most problematic factors for Russia in relation to Spain were, above all, tax regulation and inflation.